Haemato-Biochemical Alterations in Buffaloes Suffering from Uterine Torsion - Pateliya, Chintan S.; Patel, J. A.; Dhami, A. J.; Pathan, M. M. (International Journal of Livestock Research, 2019)
The study was conducted to investigate the haemato-biochemical alterations in buffaloes with uterine torsion (Gr-I, n=10) in comparison to normal parturient buffaloes Gr-II, n=6) just before parturition, at 1 hr, 1 day and 1 week after assisted or natural parturition. The cases presented to Veterinary Clinical Complex of the College in Anand and from nearby area were included in the study. Diagnosis of uterine torsion was made based on history of the case and by trans-rectal examination followed by trans-vaginal examination. All the buffaloes with uterine torsion were treated by Schaffer’s method. Uterine torsion affected buffaloes revealed significantly reduced levels of haemoglobin, packed cell volume and total erythrocytes count as compared to the normal parturient buffaloes, while total leukocyte count and differential leukocyte count, viz., neutrophils, lymphocyte, monocyte and eosinophil counts showed non-significant increase as compared to normal parturient buffaloes at different peripartum periods. The uterine torsion in buffaloes was associated with significantly reduced serum total protein, calcium and phosphorus, and elevated blood glucose, serum creatinine and urea levels as compared to normal ones. It was concluded that the serum levels of creatinine and urea at the time of presentation of a case of uterine torsion can be used as the prognostic indicators for future outcome of obstetrical management of the condition.